Prospects and Potential of Growing of Safe Vegetables Using Value Chain Approach: Case Study in Bangladesh - Tahmid, Marufa (International Journal of Psychosocial Rehabilitation, 2020)
Bangladesh has achieved impressive growth in food production over the years to meet the ever-increasing demand for food for its population, which is currently about 160 million. Though there has been impressive growth in vegetable production over the years to meet the ever-increasing demand for vegetables for its population and the inland and export market, the biggest challenge is to ensure safe food in a sustainable manner. Indiscriminate use of harmful pesticides and chemicals in the production and processing of vegetables and various other food crops and food products has made most of our food unhealthy. This has created a serious impact on the health of the population, and the prevalence of various diseases has increased. Though researchers have developed technologies to use safe practices and there exists indigenous knowledge, there is a need for strengthening the value chain of food free from harmful pesticides and chemicals and food that is not adulterated so that consumers can purchase such food with trust. In order to ensure sustainable production, there is a need to consider social, technological economical, financial, environmental and marketing aspect and work along the whole value chain starting from the production to market level. This paper concentrates on safe vegetable production using a value chain approach. Thereby, the value chain actors, their roles and relationships, key constraints in relation to inputs, production & marketing, and the corresponding activities to address the constraints and outcome/impact need to be considered.